SEJARAH (PENDIDIKAN) ISLAM MODERN DALAM PERSPEKTIF IBRAHIM M. ABU-RABI’ - Nurul Mubin (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2018)
The debate among Western academics, US politicians and security councils has intensifiedfollowing similar attacks, although not as devastating as the September 11 tragedy, somesee political Islam, especially regarding the relationship between Islam and democracy,at least divided into two major currents; the first group is a group that concludes thatIslam does not oppose democracy, the second group is a group that views Islam asopposed to democracy. This group assumes that the fundamental values of Islam arevery compatible with democracy. Islam is not anti-democratic, but between Islam anddemocracy can live side by side. Not only are Western thinkers who have views like this,not a few among Islamic scholars have this view. Ibrahim M. Abu Rabi 'in the theme of hisarticle entitled "A Post- September 11 Critical Assessment of Modern Islamic History" inthe book "September 11, Religious Perspectives on the Causa and Consequences" triedto question and then explain why there were attacks on the US by groups Muslims fromthe point of view of Qur'anic rationalization of violence. Because after all, the tragedyhas changed the West's image of Islam which has become increasingly negative and haseven reached a terrible level, the symptom of fear known as Islamamphobia. Ibrahim M.Abu Rabi 'tried to examine the tragedy in a historical perspective. This article outlinesattempts to discuss his thoughts on the important points to be elaborated, namely: 1).education in the Muslim world; modern or traditional. 2). M. Abu Rabi's Inspiration ofThought 'in the Renewal of the Islamic Education System in PTKAI and PTU.